PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN ( STUDI PADA PTPN.IX. PERSERO KEBUN MERBUH ) - Puput Musalimah, 09.05.51.0036 (Students Journal of Economic and Management, 2013)
The purposeofthe studytitled âThe Influence of Leadership, Motivation and compensation of Employee Performance in PTPN IX PerseroKebunMerbuhâ is the analysis of leadership, motivation and compensation of employer perform in PTPN IX PerseroKebunMerbuh. The sample using of research 130 reponde with data collection of methode using of research is questionnaire with the way of questionnaire list to response get information.The data were analyzedusingfactoranalysitotest thevalidity of thequestionnaireitems, Cronbachalphaformulatotest the reliability ofthe instrument, regressionanalysis, toexamine theeffect of partiallymagnitudeof eachindependent variableweretestedwith thecoefficient of determinationandtestfitthe modelto testandprovethe influence oftherespective partialfree variable. The results ofthe hypothesisare: (1) The results ofstatisticalcalculationwithlinearregressionanalysiscan beshown by theregressionequationY=X1+X2+X3. From theregressionequationis knownthat theleadership, motivationandcompensationhasa positiveand significantimpacton employee performance. (2) The calculation of the magnitude ofthe coefficient of determination. Thismeansthat theindependentvariable(leadership, motivation, andcompensation) amounted% have a roletogethercanexplain/explainthe dependentvariable(employee performance). While the remaining11.7% (100% -88.3) is explainedbyother variables thatare notusedin this study. (3) The hypothesis thathas beendonein this studywe can concludethat: A) There is apositiveand significanteffect ofleadershipon employee performance. B) There is apositiveand significanteffect ofmotivationon employee performance. C) There is apositive and significant impacton the performance ofemployeecompensation. D) There is apositive and significant impactof leadership, motivationandcompensationto employee performance.Keywords:The Leadership, Motivation, Compensation, EmployeePerformance